COMPARISON OF CEPHALOMETRIC CRANIOFACIAL FEATURES AND FACIAL PHOTOGRAPHIC FEATURES FOR TWO GENERATIONS OF PATIENTS - MIRDEHGHAN, Dr NASIM; SHARIF, Dr KANAAN; KALIA, DR AJIT; MIRDEHGHAN, Dr MASOUD; MIRDEHGHAN, DR KAZEM; KHAN, NAJNEEN NOORMOHAMMED (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2021)
Objective: To estimate the correlation and variant heritability values of craniofacial variables between parents and their offspring. Materials and Methods: The sample comprised 20 Indian families; each family consisted of father, mother, son, and daughter. Lateral cephalometric radiographs and facial photographs were taken for each family member.Fifty -three angular, linear, and proportional cephalometric variables were measured and photographic analysis was done. Interfamilial correlations and heritability (h2) values were estimated among father-son, father-daughter,mother-son, and mother-daughter pairings. Results: The most similar angular measurements between parents and offspring were as follows:SNA0,SNB0 ,ANB0 ,FMA0, MP-FH0 , LI-NB0, Op-FH0 ,UI-NA0 , OP-SN0, LI-NB0 and The most similar linear measurements were as follows: Co-Pt.A,Co-Gn, N- ANS, , UI-A, Me-Me’,LI-A.Pog, Mx 1 exposure. Both the correlation coefficients and the heritable values were stronger in the father-offspring than the mother-offspring pairings. Conclusions: The overall correlation and h2 mean values for the three types of measurements showed stronger values in the father-offspring than the mother-offspring groups, with the father –son pairings more significant than the father-daughter groups.   KEY WORDS: Cephalometrics; Heritability; Facial photographs; Craniofacial features; Offspring.